DEVELOPMENT OF A TECHNOLOGY-BASED INTERACTIVE FOR AGRICULTURAL INFORMATION DISSEMINATION IN THE SIDAPDAP SIMANOSOR VILLAGE FARMERS' GROUP - Romia Lubis; Selvia Djasmayena; Septriana Sari; Cyntia Rivatunisa; Muhammad Reyan Dirul Adha (JURNAL TEKNISI, 2025)
Abstract: Sidapdap Simanosor Village Farmers Group faces challenges in accessing and managing agricultural information efficiently. Limited resources and the absence of a web-based platform hinder the distribution of information quickly and accurately. This study aims to develop a technology-based agricultural forum site to improve the accessibility of information for farmer groups. The method used is the Waterfall software development model, which includes needs analysis, design, implementation, testing, and maintenance. The results of the study indicate that the agricultural forum website can function well and provide convenience for farmer group members in accessing information, sharing experiences, and increasing collaboration between farmers. The implementation of this information technology has been proven to increase the efficiency of the agricultural information system, support sustainable agricultural practices, and encourage the growth of the agricultural sector in the area.Keywords: farmer groups, agricultural information systems, agricultural websites.Â Abstract: Kelompok Tani Desa Sidapdap Simanosor menghadapi tantangan dalam mengakses dan mengelola informasi pertanian secara efisien. Keterbatasan sumber daya dan tidak adanya platform berbasis web menghambat distribusi informasi yang cepat dan akurat. Penelitian ini bertujuan untuk mengembangkan situs forum pertanian berbasis teknologi guna meningkatkan aksesibilitas informasi bagi kelompok tani. Metode yang digunakan adalah model pengembangan perangkat lunak Waterfall, yang meliputi analisis kebutuhan, perancangan, implementasi, pengujian, dan pemeliharaan. Hasil penelitian menunjukkan bahwa situs web forum pertanian dapat berfungsi dengan baik dan memberikan kemudahan bagi anggota kelompok tani dalam mengakses informasi, berbagi pengalaman, serta meningkatkan kolaborasi antarpetani. Implementasi teknologi informasi ini terbukti meningkatkan efisiensi sistem informasi pertanian, mendukung praktik pertanian berkelanjutan, serta mendorong pertumbuhan sektor pertanian di daerah tersebut.Keywords: kelompok tani, sistem informasi pertanian, situs web pertanian.